Peran Kualitas Pelayanan dalam Meningkatkan Kepuasan Konsumen Pemesanan Tiket Kereta Api Jarak Jauh Melalui Aplikasi KAI Access Ditinjau dari Perspektif Marketing Syariah - Nia Rifanda Putri; Teguh Lesmana; Eva Yuniarti Utami; Musran Munizu; Nersiwad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In this modern era, all fields are required to move faster so time is considered very valuable in this era. Therefore, transportation as a tool used by humans to travel is also required to be improved so that it can be faster and more comfortable. The aim of this research is to find out whether service quality influences consumer satisfaction when ordering long-distance train tickets via the KAI Access application. The data collection method used in this research is by using a questionnaire, which is a data collection technique that is carried out by giving a set of questions or statements to consumers or users of the KAI Access application. The data analysis method in this research uses descriptive analysis, simple regression and coefficient of determination. The research results show that service quality has a significant effect on consumer satisfaction when ordering train tickets via the KAI Access application. This is known from the results of the t test where the t count of 9.017 is greater than the t table value of 1.984 or can be seen from the significant value of 0.000 < 0.05.